Association of blood pressure with short- and long-term functional outcome after stroke thrombectomy: post hoc analysis of the SIESTA trial - Schönenberger, Silvia; Uhlmann, Lorenz; Ungerer, Matthias; Pfaff, Johannes; Nagel, Simon; Klose, Christina; Bendszus, Martin; Wick, Wolfgang; Ringleb, Peter A.; Kieser, Meinhard; Möhlenbruch, Markus Alfred; Bösel, Julian (Stroke, 2018)
Background and Purpose—Outcome after mechanical thrombectomy for ischemic stroke may be influenced by blood pressure (BP). This study aims to assess the association of BP changes during general anesthesia versus conscious sedation with functional outcome after mechanical thrombectomy.Methods—SIESTA (Sedation vs Intubation for Endovascular Stroke Treatment) was a monocentric randomized trial of general anesthesia versus conscious sedation during mechanical thrombectomy involving BP target protocols. In this post hoc analysis, BP measurements were divided into 4 phases: preintervention, prerecanalization, postrecanalization, and postintervention. We examined the association between BP and functional outcomes (defined by improvement of 24-hour National Institutes of Health Stroke Scale [NIHSS] and 3-month modified Rankin Scale).Results—We found no association between the difference in systolic BP, diastolic BP, and mean arterial pressure from baseline to the different phases of intervention and NIHSS change after 24 hours. Only baseline diastolic BP was associated with a reduced improvement in NIHSS (β=0.17, P<0.01). There was no association of BP drops with a change in modified Rankin Scale at 3 months. About sedation, only baseline mean arterial pressure preintervention revealed significant associations (β=0.16, P<0.01) with less change in 24-hour NIHSS in conscious sedation group. Otherwise, there was no association for differences of any of the BP measurements with a change in 24-hour NIHSS and long-term functional outcome either in general anesthesia or the conscious sedation group when analyzed separately, consistent with our findings in the entire cohort. Doses of propofol (β=0.84, P=0.04) and norepinephrine (β=1.87, P=0.01) administered during intervention before recanalization were associated with reduced improvement of NIHSS at 24 hours.Conclusions—In a setting, where both sedation regimes general anesthesia and conscious sedation were performed according to strict protocols directed at avoiding BP extremes, our findings suggest that peri-interventional BP drops were not associated with either early neurological improvement or long-term functional outcome.Clinical Trial Registration—URL: https://www.clinicaltrials.gov. Unique identifier: NCT02126085.
accepted 22 March 2018
Gesehen am 16.04.2020